2015
DOI: 10.1016/j.contraception.2014.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Did increasing use of highly effective contraception contribute to declining abortions in Iowa?

Abstract: Declines in abortion followed increases in LARC use in Iowa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
50
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 23 publications
(33 reference statements)
1
50
0
Order By: Relevance
“…Multiple factors influence the incidence of abortion. These factors include access to health care services, including contraception (82)(83)(84); the availability of abortion providers (14,15,(85)(86)(87); state regulations, such as mandatory waiting periods (88), parental involvement laws (89), and legal restrictions on abortion providers (90,91); increasing acceptance of nonmarital childbearing (92,93); shifts in the racial/ethnic composition of the U.S. population (94,95); and changes in the economy and the resulting impact on fertility preferences and use of contraception (96,97). However, because unintended pregnancy precedes nearly all abortions (26), ¶ ¶ ¶ ¶ ¶ efforts to reduce the incidence of abortion need to focus on helping women, men, and couples avoid pregnancies that they do not desire.…”
Section: Public Health Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple factors influence the incidence of abortion. These factors include access to health care services, including contraception (82)(83)(84); the availability of abortion providers (14,15,(85)(86)(87); state regulations, such as mandatory waiting periods (88), parental involvement laws (89), and legal restrictions on abortion providers (90,91); increasing acceptance of nonmarital childbearing (92,93); shifts in the racial/ethnic composition of the U.S. population (94,95); and changes in the economy and the resulting impact on fertility preferences and use of contraception (96,97). However, because unintended pregnancy precedes nearly all abortions (26), ¶ ¶ ¶ ¶ ¶ efforts to reduce the incidence of abortion need to focus on helping women, men, and couples avoid pregnancies that they do not desire.…”
Section: Public Health Implicationsmentioning
confidence: 99%
“…Although use of intrauterine devices and implants has increased in recent years, use of these methods remains low in comparison with use of oral contraceptives and condoms, both of which are less effective at preventing pregnancy (99,101). Research has indicated that providing contraception for women at no cost can increase use of these methods and reduce abortion rates (82)(83)(84) § Percentage is calculated as the number of abortions reported by known age divided by the sum of abortions reported by known and unknown age. ¶ Because reporting is not mandatory, a complete number of abortions performed in the District of Columbia could not be obtained.…”
Section: Public Health Implicationsmentioning
confidence: 99%
“…The majority of reported abortions in 2014 were among women with a previous birth or previous induced abortion, events that also are opportunities for contraception counseling and initiation; contraception provision in the immediate postpartum and postabortion settings might increase access to methods considered safe for many women (106). Additionally, providing contraception for women at no cost can increase use of these methods and reduce abortion rates (87)(88)(89) § § Reporting area reported abortion numbers for both in-state and out-of-state residents; for out-of-state residents, the state or area of residence was not provided. ¶ ¶ Data from hospitals and licensed ambulatory care facilities only; because reporting is not mandatory for private physicians and women's centers, a complete number of abortions performed in New Jersey could not be obtained.…”
Section: Public Health Implicationsmentioning
confidence: 99%
“…Multiple factors influence the incidence of abortion, including access to health care services and contraception (87)(88)(89); the availability of abortion providers (8,9,50,90-92); state regulations, such as mandatory waiting periods (68), parental involvement laws (93), and legal restrictions on abortion providers (94,95); increasing acceptance of nonmarital childbearing (96,97); shifts in the race/ethnicity composition of the U.S. population (98,99); and changes in the economy and the resulting impact on fertility preferences and use of contraception (100,101). However, despite the multiple influences on abortion, because unintended pregnancy precedes nearly all cases of abortions, ¶ ¶ ¶ ¶ ¶ efforts to reduce the incidence of abortion need to focus on helping women, men, and couples avoid pregnancies that they do not desire.…”
Section: Public Health Implicationsmentioning
confidence: 99%
“…[4][5][6][7] Hormonal contraceptives are convenient and effective resources that allow women to plan and space pregnancies. [8][9][10][11][12][13][14][15][16][17][18] Long-acting reversible contraceptives (LARC), including intrauterine devices and subdermal implants, are the most effective nonpermanent methods to prevent unintended pregnancy and thus to support women in timing and spacing their pregnancies. 11,[15][16][17][18] Currently, hormonal contraceptives are available via several routes of administration: oral, vaginal, transdermal, injection, dermal patch, intrauterine or subdermal implants.…”
mentioning
confidence: 99%